WAYS OF IMPROVEMENT OF PHARMACOTHERAPY OF EPILEPSY AT CHILDREN: FOCUS ON SPECIFIC FEATURES OF BIOTRANSFORMATION MEDICINES - B. I. Kantemirova; A. K. Starodubtsev; D. A. Sychev; V. V. Belopasov; Zh. M. Tsotsonava; V. I. Griganov (Эпилепсия и пароксизмальные состояния)
For the first time at children of five various nationalities living in the territory of the Astrakhan region, polymorphism of a gene of CYP2C19 on a polymorphic marker of G681A is studied. Statistically authentic distinction in frequencies of occurrence of genotypes of CYP2C19 associated both with fast, and with a slow metabolism of medicinal means substrata that testifies to importance of individual studying of polymorphism of CYP2C19 is revealed. It is studied, on restored glutathione blood, activity of the second phase of biotransformation of anti-epileptic preparations. Offers on improvement of pharmacotherapy of epilepsy at children are created.